2022
DOI: 10.1038/s41598-022-14585-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards a general approach for tailoring the hydrophobic binding site of phenylalanine ammonia-lyases

Abstract: Unnatural substituted amino acids play an important role as chiral building blocks, especially for pharmaceutical industry, where the synthesis of chiral biologically active molecules still represents an open challenge. Recently, modification of the hydrophobic binding pocket of phenylalanine ammonia-lyase from Petroselinum crispum (PcPAL) resulted in specifically tailored PcPAL variants, contributing to a rational design template for PAL-activity enhancements towards the differently substituted substrate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Note that the assessment of the intracellular PAL concentration of whole-cell biocatalysts is challenging; therefore, direct comparison of conversion-based catalytic efficiencies of whole-cell biocatalysts and purified PALs should be treated cautiously. In general, the conversion values provided by the purified Pc PALs and the corresponding At PALs are of similar range (Table ), in accordance with their similar k cat values (equivalent to turnover frequencies), determined by enzyme kinetic measurements . However, whole-cell At PALs outperformed their Pc PAL homologues in terms of conversion values (Table ), despite both recombinant PALs being expressed under identical conditions from similar recombinant plasmid constructs, supporting a higher operational stability of the At PAL whole-cell biocatalysts.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Note that the assessment of the intracellular PAL concentration of whole-cell biocatalysts is challenging; therefore, direct comparison of conversion-based catalytic efficiencies of whole-cell biocatalysts and purified PALs should be treated cautiously. In general, the conversion values provided by the purified Pc PALs and the corresponding At PALs are of similar range (Table ), in accordance with their similar k cat values (equivalent to turnover frequencies), determined by enzyme kinetic measurements . However, whole-cell At PALs outperformed their Pc PAL homologues in terms of conversion values (Table ), despite both recombinant PALs being expressed under identical conditions from similar recombinant plasmid constructs, supporting a higher operational stability of the At PAL whole-cell biocatalysts.…”
Section: Resultssupporting
confidence: 73%
“…While the catalytic site residues of At PAL and Pc PAL are identical and share high 81% sequence identity, our previous and current study revealed that At PAL variants I461V, L133A, and L257V outperformed in terms of catalytic efficiency (including substrate/product inhibition issues) the corresponding PcPAL variants. Since no structural data for At PAL exists, and our protein crystallization efforts have been hindered by the high aggregation tendency at elevated concentration of the purified enzyme, we can only suppose that structural differences not related to the catalytic site influence the different behavior of the two PALs.…”
Section: Resultsmentioning
confidence: 43%
See 3 more Smart Citations